Enhancement of Cr(VI) ion adsorption by two-step grafting of methacrylamide (MAAm) and 2-(dimethylamino)ethyl methacrylate (DMAEMA) onto polyethylene plate. Issue 13 (7th June 2022) - Kitao, Yoshinori; Kimura, Yuji; Asamoto, Hiromichi; Minamisawa, Hiroaki; Yamada, Kazunori
ABSTRACT: Polyethylene (PE) plates grafted with a neutral hydrophilic monomer, methacrylamide (MAAm), and a cationic monomer, 2-(dimethylamino)ethyl methacrylate (DMAEMA), (PE-g-PMAAm)-g-PDMAEMA plates, were prepared by the two-step photografting. The Cr(VI) ion adsorption of the resultant (PE-g-PMAAm)-g-PDMAEMA plates was investigated as a function of the initial pH value, temperature, and grafted amounts of PMAAm and PDMAEMA. The adsorption capacity of the (PE-g-PMAAm)-g-PDMAEMA plates had the maximum at the initial pH value of 3.0 and the initial adsorption rate increased with the temperature and increased with the amount of grafted DMAEMA. This result suggests that protonated dimethylamino groups present in the inside of the grafted layer are increasingly involved in the Cr(VI) ion adsorption by the increase in the water absorptivity through the formation of the intermediate grafted layer of PMAAm. The maximum adsorption ratio of 0.510 was obtained for a (PE-g-PMAAm)- g -PDMAEMA plate with G MAAm  = 30 μmol/cm 2 and G DMAEMA  = 1.7 μmol/cm 2 . The maximum adsorption capacity obtained in this study was comparable to or higher than those of other adsorbents for Cr(VI) ions. The adsorption behaviour obeyed the pseudo-second order kinetic model and was well described by the Langmuir isotherm model, suggesting that the adsorption of Cr(VI) ions occurs through the electrostatic interaction between protonated dimethylamino groups and HCrO 4 − ions. Cr(VI) ions were successfully desorbed in such eluents as NaCl, NaCl containing NaOH, NH4 Cl, NH4 Cl containing NaOH, and NaOH and (PE-g-PMAAm)-g-PDMAEMA plates were repeatedly used without considerable loss in the adsorption capacity. GRAPHICAL ABSTRACT: UF0001